SQ3R IMPLEMENTATION IN TEACHING READING COMPREHENSION A Case Study of Eight Grade Students at One State MTs in Sumedang - Mila Siti Masruuroh (Journal of English and Education, 2015)
This research aimed to describe the implementation of SQ3R in teaching reading comprehension and to identify students’ responses toward the implementation of SQ3R. Moreover, it examined the benefits of SQ3R in teaching reading comprehension in Indonesia. This research used a qualitative case study conducted at one State MTs in Sumedang. It involved one class of the eighth grade which consists of 30 students. The data were collected through observation, interview, and document analysis. The data from the three instruments were analyzed qualitatively. The results of this research showed that the implementation of SQ3R helped the students to comprehend English texts. The students also responded the implementation of SQ3R positively. They focused while reading English texts by using SQ3R. They were also interested and enthusiastic in doing the tasks. In addition, SQ3R helped them to write questions from the texts, to rewrite the information by their own words, to write a report or a summary about the texts, and to enrich their vocabularies. In conclusion, SQ3R helped the students in reading English texts. Therefore, SQ3R is recommended to be implemented in teaching reading comprehension.